EFEKTIVITAS KONSELING REALITAS UNTUK MENINGKATKAN SELF ESTEEM ANAK KORBAN BULLYING - Afan Rif’at Murat; Muhammad Japar; Nofi Nur Yuhenita (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2023)
This study aims to examine the effect of individual counseling with a reality approach on the self-esteem of children who are victims of bullying. This study uses a one group pretest and posttest design. The sampling technique used was purposive sampling, namely the youth of Dusun Gendolsari who had low self-esteem characteristics. The samples taken in this study were 5 people. The method of data collection is done by using a self-esteem questionnaire. The data analysis method used is the paired sample t-test parametric analysis. The results of this study indicate that individual counseling with a reality approach has an effect on increasing self-esteem. This is evidenced by the t-test results of -18,634 paired samples with a probability value of sig(2-tailed) 0.000<0.05. Based on the results of the analysis and discussion, there is a difference in the average score of the self-esteem scale of 31.73% from the results of the pretest and posttest. The results of the study can be concluded that individual counseling with a reality approach has an effect on increasing the self-esteem of children who are victims of bullying.